The implementation of total quality management in vocational high schools - Rahayuningsih, Retna Sundari; Fajaruddin, Syarief; Manggalasari, Lena Citra (Research and Social Study Institute, 2018)
The study aimed to find out the implementation of teachers’ focus on students and the level of students’ satisfaction, the implementation of the involvement of school’s communities, the implementation of teacher service measurement, the implementation of the commitment of school’s communities, and implementation of teacher services improvement. This particular evaluative research used descriptive-quantitative design. The evaluation model was a discrepancy evaluation model. The research sites were Negeri 2 Pengasih State Vocational High School, Negeri 1 Nanggulan Kulon Program State Vocational High School, Ma’arif 1 Wates Kulon Progo Vocational High School and Muhammadiyah 1 Temon Kulon Progo Vocational High School. The subjects of this study were students, teachers, and principals from four schools. The objects of this research were: (1) the implementation of teachers’ focus on students, (2) the implementation of the involvement of school’s communities, (3) the implementation of teacher service measurement, (4) the implementation of the commitment of school’s communities, and (5) the implementation of teacher service improvement. Data collection techniques were observation, document analysis, and questionnaire. Data collection instruments used observation rubric, document analysis sheets, and questionnaire. The level of implementation reported in a percentage which reports a comparison between the averages score and the maximum score. The results of this study showed that the overall average in four vocational high schools were: (1) the level of teacher's focus on students was 81.13% (very good), and the level of students’ satisfaction was 77.69% (students feel satisfied); (2) the level of involvement of school’s communities was 80.28% (good); (3) the level of teacher service measurement was 77.50% (good); (4) the level of the commitment of school’s communities was 79.77% (good); and (5) the level of teacher service improvement was 77.50% (good).Keywords: total quality management, vocational high school